Coccidioidomycosis: first cases reported in Pernambuco, Brazil - Araújo, Paulo Sergio Ramos de (2018)
Coccidioidomycosis is a fungal infection caused by Coccidioides immitis or Coccidioides posadasii. These fungi are known to thrive in desert climate. Fungi produce infectious arthroconidia in soil, they are aerosolized in the air and when inhaled by humans, usually cause infections such as pneumonia. The first cases of coccidioidomycosis in Brazil were reported in 1978. Since then, there have been other reports mainly from desert regions of Northeastern Brazil. The present report describes three cases of coccidioidomycosis on male farmers from Serra Talhada county, Pernambuco State, who developed pneumonia and were subsequently diagnosed with pulmonary coccidioidomycosis. These three farmers were successfully treated with oral fluconazole. They reported having hunted armadillos in a rural and arid area of Pernambuco State. Armadillos are known to be carriers of Coccidioides. This is the first report of infection caused by Coccidioides in Pernambuco State, Brazil.